Follow the data: administering science at Edward Sabine's magnetic department, Woolwich, 1841–57. (17th October 2018) - Goodman, Matthew
Abstract : This paper considers the transmission of magnetic observations from overseas, colonial, observatories and the removal of these data from manuscripts to become the printed results of the so-called magnetic crusade, between 1841 and 1857. The processes adopted by Edward Sabine's magnetic department at Woolwich Arsenal to cope with the accumulation of very literal masses of data are considered, as well as the politicking that attended Sabine's attempts to have this department installed within the space occupied by, and the bureaucracy of, the Board of Ordnance. The magnetic crusade was one of the largest data-collecting enterprises of the nineteenth century, and a history of its data-management processes provides an important contribution to recent attempts to historicize discussions about Big Data and perceptions of information overload.